Algoritmo heurístico construtivo em estrutura multipartida aplicado no planejamento da expansão de sistemas de distribuição - Almeida, Matheus de (2022)
This work presents a constructive heuristic algorithm in multi-start structure applied to planning the expansion of medium voltage overhead distribution lines to supply electricity to current and future customers. Such algorithm, through its multi-start feature, is able to establish a set of feasible radial topologies, considering the lowest construction costs, lowest electrical losses and better system voltage profile. To achieve this goal, the algorithm considers normalized weights and random numbers aiming at a broader search field for solution. The problem is represented by a nonlinear mathematical model and the solution is constructively obtained in an iterative way. At each iteration, a sensitivity indicator is used to indicate which circuit to build at that instant. The constructive heuristic algorithm in multi-start structure was implemented using the algebraically oriented language called GAMS. Computational tests were performed to evaluate the algorithm's performance. The results obtained in the simulations showed that the algorithm finds a set of feasible and good quality solutions.